The adventurer's guide to treasure (and how to steal it) - White, Wade Albert (White, Wade Albert. Adventurer's guide, 2019)
"Anne, Penelope, and Hiro are tasked once again with an impossible quest to save the world, leading them on a mission to defeat the supreme leader of pirates, rescue dear friends, and solve the riddle of Anne's mysterious heritage"--